The Making of an Arctic Naturalist - Salomonsen, Finn (ARCTIC, 1973)
One of the greatest impressions of my life was my first visit to Greenland. I was a mere boy at that time, only sixteen years old . This visit to Greenland changed my life. I lost my heart to the Arctic and realized that I must return to learn more of the secrets behind the Polar beauty. This was not my birth as a naturalist, to be sure, since from early boyhood I had wanted to study nature and its creatures, but during this Greenland trip I received a special challenge: my endeavours were now directed towards a distinct though faraway goal. . When in 1925 at the age of sixteen I joined Schiøler's Greenland expedition I had been a member of the Danish Ornithological Society and the Danish Natural History Society for two years, admittedly an extraordinarily young member. . I was interested in most animal groups, although favouring birds and various marine invertebrates. During that time I made the acquaintance of Dr. C. G. Johs. Petersen, director of the "Biological Station", in those days the Danish institute for marine biological research. . I spent many evenings in Dr. Petersen's home, learning and discussing marine zoology. I was seriously inclined to choose that field, rather than ornithology, as my future specialty, until I met Ejler Lehn Schiøler, and one year later received the offer to accompany him to Greenland. Schiøler was a remarkable man. He was a banker who became very wealthy but in his spare time he was an ardent student of ornithology and succeeded in gathering a collection of more than 25,000 skins of western palearctic birds, besides skeletons and eggs. He built a large museum for his collections with an ornithological library. . Naturally, I admired this great scientist, and in his study, when he showed me his birds and told me about the problems they posed, I gradually decided to be an ornithologist. When we left for Greenland in 1925, altogether five men, in order to collect and study the birds of the west coast, it was still the old regime. The native population lived literally under ...